2010
DOI: 10.14311/1287
|View full text |Cite
|
Sign up to set email alerts
|

Color Portion of Solar Radiation in the Partial Annular Solar Eclipse, October 3rd, 2005, at Helwan, Egypt

Abstract: Measurements were made of various solar radiation components, global, direct and diffuse and their fractions during the partial annular solar eclipse on October 3rd, 2005 at Helwan, Egypt (Lat. 29.866◦ N and Long. 31.20◦ E), and an analysis has been made. The duration of the solar eclipse was 3 h 17 min, and the maximum magnitude of the eclipse in this region was 0.65. The optical depth of the direct component and the relative humidity decreased, while both the transparency and the air temperature increased to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For the eclipse of 2005, Hassan et al (2010) [159] found at Helwan that at maximum eclipse, optical depth decreased while transparency improved. The air temperature decreased by an amount of 1.8 • C and a 2% increase in RH was recorded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the eclipse of 2005, Hassan et al (2010) [159] found at Helwan that at maximum eclipse, optical depth decreased while transparency improved. The air temperature decreased by an amount of 1.8 • C and a 2% increase in RH was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them have been observed from countries of northern Africa and from the Near-East. Measurements of the atmospheric response during the annular solar eclipse of 3 October 2005 have been reported in these regions by [159] in Egypt, and by Anbar (2006) [118] in Saudi Arabia. Also during the total solar eclipse of 29 March 2006, measurements made by Möllman and Vollmer (2006) [160], Uddin et al (2007) [123], Pintér et al (2008), Pleijel (2008) [20] and Stoev et al (2008Stoev et al ( , 2012 [122,161] in Turkey, by Nawar et al (2007) [162] in Egypt, by [119] in Libya and, by Nymphas et al (2009) [163] in Nigeria, were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation